2016
DOI: 10.1007/s00276-016-1664-3
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomographic evaluation of nutrient canals and foramina in the anterior region of the mandible

Abstract: The present study revealed the frequency and distribution of NCs using CBCT image analysis. NCs are important because surgical injury to the neurovascular bundle within these canals can lead to excessive bleeding and postoperative paresthesia. The identification of NC on CBCT images may be useful during the harvesting of bone blocks or placement of endosseous implants in the anterior region of the mandible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
2
5
0
2
Order By: Relevance
“…The results showed that there was a relationship between foramen diameter and sex, with larger diameters found among male individuals than among female individuals. An MLF diameter between 1.0 mm and 3.2 mm has been reported elsewhere [17,20]. In our sample, foramina with a diameter greater than 1.0 mm were observed.…”
Section: Discussionsupporting
confidence: 75%
“…The results showed that there was a relationship between foramen diameter and sex, with larger diameters found among male individuals than among female individuals. An MLF diameter between 1.0 mm and 3.2 mm has been reported elsewhere [17,20]. In our sample, foramina with a diameter greater than 1.0 mm were observed.…”
Section: Discussionsupporting
confidence: 75%
“…Different studies have reported the importance of various neurovascular anatomic structures identified on cross‐sectional imaging, including: 1) inferior alveolar (mandibular) canal; 2) anterior loop and mandibular incisive canal; 3) mental foramen; 4) lingual canal; and 5) maxillary incisive/nasopalatine canal, and highlight the variability of imaging identification and characteristics of these structures in relation to implant placement 98‐109 . Hence, efforts are underway to automate identification of the mandibular canal 110 …”
Section: Resultsmentioning
confidence: 99%
“…Different studies have reported the importance of various neurovascular anatomic structures identified on cross-sectional imaging, including: 1) inferior alveolar (mandibular) canal; 2) anterior loop and mandibular incisive canal; 3) mental foramen; 4) lingual canal; and 5) maxillary incisive/nasopalatine canal, and highlight the variability of imaging identification and characteristics of these structures in relation to implant placement. [98][99][100][101][102][103][104][105][106][107][108][109] Hence, efforts are underway to automate identification of the mandibular canal. 110 In addition, the use of CBCT has been found to be effective in locating blood vessels in the lateral wall of the maxillary sinus, which should be appreciated prior to sinus augmentation procedures.…”
Section: Use Of Cbct For Anatomic Characterizationmentioning
confidence: 99%
“…Esses canais são derivados do ramo incisivo do nervo alveolar inferior, sendo atribuídos a eles a função de promover um aporte nutrício entre os elementos neurovasculares e os dentes, como também, as suas estruturas adjacentes. Em radiografias periapicais essas composições são observadas como imagens radiolúcidas lineares entre os incisivos inferiores, que por vezes, podem ser de difícil identificação 4,5 . Um estudo recente demonstrou que a detecção dos canais nutrícios é extremamente favorecida pelo emprego de exames de TCFC 5 .…”
Section: Introductionunclassified
“…4 Doutor em Ciências da Saúde; Professor Titular da área de Diagnóstico e Cirurgia Oral do Curso de Odontologia do Centro Universitário UniEVANGÉLICA. 5 Doutora em Odontologia; Professora Adjunto da área de Diagnóstico e Cirurgia Oral do Curso de Odontologia do Centro Universitário UniEVANGÉLICA. 6 Doutor em Odontologia; Professor Titular da área de Endodontia do Curso de Odontologia do Centro Universitário UniEVANGÉLICA.…”
unclassified